2012
DOI: 10.1051/0004-6361/201118757
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the angular distribution of the cosmic microwave background

Abstract: Context. Intriguing features in the angular distribution of the cosmic microwave background (CMB), such as the north-south asymmetry, were reported in the one-and three-year Wilkinson Microwave Anisotropy Probe (WMAP) data and should be studied in detail. We investigate some of these asymmetries in the CMB temperature angular distribution considering the ΛCDM model in the three, five, and seven year WMAP data.Aims. We aim to analyze the four quadrants of the internal linear combination (ILC) CMB maps using thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Other unexpected features then emerged from the data, with examples including an alignment of the low order multipoles (Bielewicz et al 2004;Schwarz et al 2004;Copi et al 2004;de Oliveira-Costa et al 2004;Bielewicz et al 2005;Land & Magueijo 2005;Copi et al 2006;Abramo et al 2006;Frommert & Ensslin 2010;Gruppuso & Burigana 2009), the cold spot, which corresponds to a region with a significant temperature decrement (Vielva et al 2004;Cruz et al 2005Cruz et al , 2007Vielva 2010). More recently, the lack of large angle temperature correlations found previously on WMAP data were confirmed in Planck data by Copi et al (2013).The anomaly more related to this paper are the north-south asymmetry (Eriksen et al 2004a,b;Hansen et al 2004a,b;Donoghue et al 2005;Hoftuft et al 2009;Paci et al 2010;Pietrobon et al 2010;Vielva et al 2010) and the quadrant asymmetry (Santos et al 2012).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Other unexpected features then emerged from the data, with examples including an alignment of the low order multipoles (Bielewicz et al 2004;Schwarz et al 2004;Copi et al 2004;de Oliveira-Costa et al 2004;Bielewicz et al 2005;Land & Magueijo 2005;Copi et al 2006;Abramo et al 2006;Frommert & Ensslin 2010;Gruppuso & Burigana 2009), the cold spot, which corresponds to a region with a significant temperature decrement (Vielva et al 2004;Cruz et al 2005Cruz et al , 2007Vielva 2010). More recently, the lack of large angle temperature correlations found previously on WMAP data were confirmed in Planck data by Copi et al (2013).The anomaly more related to this paper are the north-south asymmetry (Eriksen et al 2004a,b;Hansen et al 2004a,b;Donoghue et al 2005;Hoftuft et al 2009;Paci et al 2010;Pietrobon et al 2010;Vielva et al 2010) and the quadrant asymmetry (Santos et al 2012).…”
Section: Introductionsupporting
confidence: 75%
“…Taking into consideration that the occurrence of this asymmetry in the data (σ SEQ /σ NEQ ) can happen between any quadrant in the simulated maps, regardless of the different number of pixels in each quadrant because of the use of the mask, we found a probability of 0.8% for this asymmetry to happen (see Table 3, probability P3). It is important to point out that Santos et al (2012) found no evidence for a connection between the SEQ excess of power and the so-called cold spot anomaly (see Vielva et al 2004;Cruz et al 2005Cruz et al , 2007Vielva 2010).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Other violations of isotropy were soon announced in WMAP data, including an alignment of the loworder multipoles (Bielewicz et al 2004(Bielewicz et al , 2005Schwarz et al 2004;Copi et al 2004Copi et al , 2006de Oliveira-Costa et al 2004;Land & Magueijo 2005;Abramo et al 2006;Gruppuso & Burigana 2009;Frommert & Ensslin 2010), the cold spot (Vielva et al 2004;Cruz et al 2005Cruz et al , 2007Vielva 2010), the parity asymmetry (Kim & Naselsky 2010;Gruppuso et al 2011;Aluri & Jain 2012;Hansen et al 2012;Naselsky et al 2012;Zhao 2014), and the north-south asymmetry (Eriksen et al 2004a,b;Hansen et al 2004a,b;Donoghue et al 2005;Hoftuft et al 2009;Paci et al 2010;Pietrobon et al 2010;Vielva et al 2010). Closely related to the north-south asymmetry is the power asymmetry found between different quadrants of the CMB sky (Santos et al 2012(Santos et al , 2014.…”
Section: Introductionmentioning
confidence: 99%